Monoclonal Antibodies against Platelet Membrane Glycoproteins IIb/IIIa and Ibα Inhibit Platelet Dependent Thrombin Generation by Different Mechanisms - Thomas, Stephen; Metcalfe, Paul; Goodall, Alison H.; Gray, Elaine (Thrombosis and Haemostasis, 2000)
The antithrombotic effect of antiplatelet agents is principally due to their anti-aggregatory action, but these agents may also interfere with coagulation. We have investigated the effect of monoclonal antibodies (MAb) to platelet membrane glycoproteins (GP) IIb/IIIa and Iba on thrombin generation.Antibodies to platelet membrane glycoprotein IIb/IIIa (RFGP56 and c7E3) were shown to inhibit platelet-mediated thrombin generation stimulated by both intrinsic and extrinsic methods. An antibody to GP Ibα (RFGP37) also inhibited thrombin generation in these systems.FITC-annexin V was used to determine the effect of these antibodies on the exposure of procoagulant phospholipids on the platelet membrane, and it was found that the anti-IIb/IIIa antibodies reduced this, whereas the anti-Ibα antibody caused an increase.We conclude that our monoclonal antibodies against platelet membrane glycoproteins IIb/IIIa and Ibα inhibit platelet dependent thrombin generation by different mechanisms.
Keywords: Platelets; glycoproteins; antibodies; thrombin generation